2018
DOI: 10.22159/ajpcr.2018.v11i3.22612
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitude Towards Stroke and Its Prevention Among Hypertensive and Non-Hypertensive People

Abstract: Objectives: objectives of the study are to compare the awareness and and attitude towards stroke and its prevention among hypertensives and nonhypertensives and compare the awareness and attitude towards stroke and its prevention among hypertensives and Non-hypertensives (2) to find out the association between the awareness and attitude toward stroke and its prevention with selected demographic variables among hypertensives and non -hypertensives.Methods: Descriptive survey design was adopted for the study. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…This result is inconsistent with some other international studies that showed most hypertensive participants had a neutral attitude toward stroke prevention approaches (Sinha et al, 2020). For example, this result is inconsistent with a study conducted in India that showed a relatively high attitude score of hypertensive people than the non-hypertensive people towards stroke prevention (Sreejesh et al, 2018). Our result could be contributed to the previous result where most participants had a poor level of knowledge, which may influence their behaviors and attitudes towards stroke prevention.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is inconsistent with some other international studies that showed most hypertensive participants had a neutral attitude toward stroke prevention approaches (Sinha et al, 2020). For example, this result is inconsistent with a study conducted in India that showed a relatively high attitude score of hypertensive people than the non-hypertensive people towards stroke prevention (Sreejesh et al, 2018). Our result could be contributed to the previous result where most participants had a poor level of knowledge, which may influence their behaviors and attitudes towards stroke prevention.…”
Section: Discussioncontrasting
confidence: 99%